Between the 'yellow-skinned enemy' and the 'black-skinned slave': early modern genealogies of race and slavery in Sa`dian Morocco. Issue 2 (4th March 2023) - Errazzouki, Samia
ABSTRACT: This paper situates Morocco's invasion of the West African Songhai Empire in 1591 within the global histories of race, slavery, and capitalism. Morocco's invasion, which took place during the height of the Sàdi dynasty (1554–1659), provided Morocco with an influx of capital through Black West African slave labour on Morocco's sugar plantations and its newfound control over the lucrative gold and salt mines of West Africa. Such wealth and power bolstered Morocco's regional and global position in the vital node where Africa, Europe, the Mediterranean, and Atlantic all converge. This paper will address the following questions: how did Morocco's shift from enslaving non-Muslims to enslaving Muslim West Africans from the Songhai based on their race lay down the foundations for centuries of anti-Black violence in North Africa? (2) how did Black slave labour from the Songhai allow Morocco to become England's primary source of sugar imports prior to the rise of sugar plantations in the Americas and the Caribbean? (3) how can we move beyond normative taxonomies that view North and West Africa as separate spaces instead of as regions whose conditions were shaped by one another? Ultimately, my paper will demonstrate how the Sàdi dynasty was an active player in the rise of racialized forms of slavery that eventually dominated the Atlantic for centuries and whose afterlives continue to endure on both sides of the Atlantic.